2020
DOI: 10.1007/s42729-020-00287-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Phosphorus (P) Uptake and Yield of Rainfed Wheat Fed with P Fertilizer by Drought-Tolerant Phosphate-Solubilizing Fluorescent Pseudomonads Strains: a Field Study in Drylands

Abstract: Application of phosphate-solubilizing bacteria (PSB) to improve phosphorus (P) nutrition of plants under conditions of P deficit in soil has been frequently studied in controlled conditions. However, little research attention has been paid to studying the combined effects of PSB and P fertilizer on improving P uptake and yield of rainfed wheat plant under natural conditions in arid and semi-arid regions including drylands. Field experiments were arranged in a randomized complete block design with a 3 × 4 × 2 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 66 publications
2
10
0
1
Order By: Relevance
“…Some researchers advocate that, under conditions of waterdeficit stress, plant accumulated proline to protect itself from its negative effects or to help preserve osmotic potential, eliminating free ROS radicals, protecting macromolecules from denaturation, and regulating cellular pH (Shirmohammadi et al 2020). In the present study, under drought stress conditions, proline content in leaves of sensitive cultivars accumulated more than tolerant ones, and exogenous application of both hormones supplied proline content in leaves of the sensitive cultivar.…”
Section: Discussionmentioning
confidence: 46%
“…Some researchers advocate that, under conditions of waterdeficit stress, plant accumulated proline to protect itself from its negative effects or to help preserve osmotic potential, eliminating free ROS radicals, protecting macromolecules from denaturation, and regulating cellular pH (Shirmohammadi et al 2020). In the present study, under drought stress conditions, proline content in leaves of sensitive cultivars accumulated more than tolerant ones, and exogenous application of both hormones supplied proline content in leaves of the sensitive cultivar.…”
Section: Discussionmentioning
confidence: 46%
“…These bacteria may also decrease the production of abscisic acid (Naz et al, 2009 ); in this way, they reduce the negative effects of stress on stomatal conductance, photosynthesis, and plant sensitivity to water deficiency (Etesami and Beattie, 2018 ). It seems that the plants inoculated with the bacterial strains have the ability to change the structure of the lateral root system and increase RWC (Bertrand et al, 2015 ; Shirmohammadi et al, 2020 ). Increased leaf RWC under stress in plants inoculated with PGPB has also been reported in other studies (Ilyas et al, 2020 ; Shilev, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In field experiments with phosphate solubilizing microorganisms and phosphate fertilization on wheat yield, Shirmohammadi et al (2020) stated that the best results occur when phosphate fertilization is associated with microorganisms. In corn inoculated with Bacillus strains, Sousa et al (2020) stated that the results are better with the association of phosphate fertilization since the bacteria enhance the effect of phosphate fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the ability of benefic microorganisms to promote plant development, specifically Pseudomonas in wheat and soybean (Afzal et al, 2010;Karimzadeh et al, 2020;Shirmohammadi et al, 2020), Bacillus strains on millet, corn and oil palm (Ribeiro et al, 2018;Lima et al, 2020, Sousa et al, 2020, Trichoderma in soybean (Bononi et al, 2020), arbuscular mycorrhiza in rice, corn and tomato (Zhang et al, 2016;Saia et al, 2020), among others. Also, these microorganisms, in most cases, are of the "multifunctional" type and can bring benefits to plants through multiple mechanisms of direct and indirect stimulation (Sobral et al, 2018;Silva et al, 2020), with the capacity to fix atmospheric nitrogen (Döbereiner, 1997), potassium solubilization (Basak et al, 2022), siderophore production (Yadav et al, 2020) and mitigation of biotic and abiotic stresses (Leite et al, 2019;Wang et al, 2020;Oliveira et al, 2021).…”
Section: Introductionmentioning
confidence: 99%